Edukasi Ampas Tahu Sebagai Bahan Pangan Tambahan Produk Nata De Soya - Harun, Nurhidayati; Kurniasih, Nia; Susan Sintia; Saleh, Ridwan Rahman (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2024)
The utilization of whey tofu is rarely known by the public. Chemical composition analysis of whey tofu shows that whey tofu media is suitable for the growth of lactic acid bacteria because it still contains a certain amount of nitrogen that can be utilized for the survival of bacteria. This community service aims to provide valuable information to the community regarding the benefits of whey tofu for microorganisms that support digestive health. This community service method involves providing education to the community of the Aisyiyah Branch Leadership in the Pamarican District. The results of the education provide mothers with an understanding of the importance of utilizing whey tofu, which can maintain digestive health